MANAJEMEN ASUHAN KEPERAWATAN PREHOSPITAL GAWAT DARURAT Tn. T DENGAN KERACUNAN ORGANOFOSFAT DI AREA KERJA PUBLIC SAFETY CENTER (PSC) 119 KABUPATEN BANTAENG : STUDI KASUS - winarti, winarti (STIKES Pasapua Ambon, 2023)
Introduction: Organophosphate intoxication can cause decreased consciousness, life-threatening airway obstruction, shock, seizures, and even death. Objective: To provide an overview and authentic experience of prehospital emergency nursing care management with organophosphate intoxication in the work area of the Public Safety Center (PSC) 119 Bantaeng Regency. Methods: used is a case study of prehospital emergency nursing care management with organophosphate intoxication by using a primary survey in providing treatment including Arway, Breathing, Circulation, Disability, and Exposure. Results: Researchers see no gap between the theory and practice of patients with organophosphate intoxication. Recommendation: A public health service system that should be imitated by other regions in improving health services to the community.